2021
DOI: 10.1186/s12967-021-02967-3
|View full text |Cite
|
Sign up to set email alerts
|

tRNA derived fragment (tRF)-3009 participates in modulation of IFN-α-induced CD4+ T cell oxidative phosphorylation in lupus patients

Abstract: Background Accumulating evidence suggests tRNA-derived fragments (tRFs) play important roles in cellular homeostasis. Here we aimed to explore aberrant expression of tRFs in CD4+ T cells from patients with systemic lupus erythematosus (SLE) and their potential function in the SLE pathogenesis. Methods First, small RNA sequencing was performed on CD4+ T cells from four SLE patients and three healthy controls (HCs). Candidate tRFs were then validated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…More precisely, Geng et al (2021) showed that tRF-3009 was substantially over-expressed in CD4 + T cells of SLE patients than those of healthy donors. What’s more, tRF-3009 may be involved in SLE pathogenesis by modulation of IFN-α-induced CD4 + T cell oxidative phosphorylation ( Geng et al, 2021 ). As for the EV, Dou et al (2021) revealed that mesenchymal stem cell (MSC)-derived EV tsRNA-21109 inhibited the M1-type polarization of macrophages, offering a promising therapeutic strategy for SLE ( Dou et al, 2021 ).…”
Section: Role Of Evs In Sle and Lnmentioning
confidence: 96%
See 1 more Smart Citation
“…More precisely, Geng et al (2021) showed that tRF-3009 was substantially over-expressed in CD4 + T cells of SLE patients than those of healthy donors. What’s more, tRF-3009 may be involved in SLE pathogenesis by modulation of IFN-α-induced CD4 + T cell oxidative phosphorylation ( Geng et al, 2021 ). As for the EV, Dou et al (2021) revealed that mesenchymal stem cell (MSC)-derived EV tsRNA-21109 inhibited the M1-type polarization of macrophages, offering a promising therapeutic strategy for SLE ( Dou et al, 2021 ).…”
Section: Role Of Evs In Sle and Lnmentioning
confidence: 96%
“…In a recent study, Xu et al (2020) found that tRNAs and tsRNAs were significantly differentially expressed in the PBMCs of SLE patients, compared with those of healthy donors, and the targeted genes of the differentially expressed tsRNAs were enriched in the signaling pathway involved in primary immunodeficiency, T cell receptor and Th cell differentiation, suggesting that tRNAs and tsRNAs play important roles in the pathogenesis of SLE (Xu et al, 2020). More precisely, Geng et al (2021) showed that tRF-3009 was substantially over-expressed in CD4 + T cells of SLE patients than those of healthy donors. What's more, tRF-3009 may be involved in SLE pathogenesis by modulation of IFN-α-induced CD4 + T cell oxidative phosphorylation (Geng et al, 2021).…”
Section: Evs Tsrna Slementioning
confidence: 99%
“…In GO and KEGG pathway analyses, tsRNAs and their related target genes were established to be enriched in immune response and immune system processes, as well as in signaling pathways such as Th1 and Th2 cell differentiation, T-cell receptor [ 95 ]. tRF-3009 from tRNA-Lue-TAA was first reported by Geng et al, who found that it was highly expressed in CD4 + T cells in SLE and positively correlated with SLE disease activity indices, lupus nephritis, and serum IFNα levels [ 96 ]. Mechanistically, tRF-3009 levels, in tandem with ATP and ROS levels, were elevated by IFNα treatment.…”
Section: Roles In Diseasementioning
confidence: 99%
“…Mechanistically, tRF-3009 levels, in tandem with ATP and ROS levels, were elevated by IFNα treatment. Upon tRF-3009 knockdown, IFN-α-induced ROS and ATP were inhibited [ 96 ]. These findings imply that tRF-3009 may be involved in SLE development by regulating IFN-α-induced oxidative phosphorylation (OXPHOS) of CD4 + T cells [ 96 ].…”
Section: Roles In Diseasementioning
confidence: 99%
See 1 more Smart Citation